Coaching in portugal: where it comes from and where it goes - a vision from the professionals - Fontes, A.; Dello Russo, S. (IV Simpósio Formação e Desenvolvimento Organizacional, 2018)
Coaching practices are increasingly spread across the world and Portugal represents no exception. If worldwide is a profession with several decades of history, in Portugal is considered as a recent profession. Given the established effectiveness of this practice, notwithstanding a number of critiques particularly related to the difficulty of explaining its effectiveness as well as to its replicability, we aimed to better understand the coaching context in Portugal. This descriptive study was based on an online survey made with a final sample of 187 for coaching practitioners. The survey had 22 questions grouped in six different sections: demographics, experience and training of the coach, coaching practices and theoretical approach, clients’ characteristics, obtained results and future trends. The majority of the questions were semi closed, except some questions related with theoretical approach, techniques used and final comments. Findings show that the majority of respondents adopt theoretical frameworks rooted in psychology or NLP and these professionals tend to adopt specific techniques/tools, particularly for diagnostic purposes. Nevertheless, the use of specific tools that would make the practice of coaching more “replicable” or “testable” is not commonly spread, especially in more advanced phases of coaching programs. Among the positive consequences of coaching, coaches report most impact on self-awareness and hope/optimism, and less on leadership competencies, despite leadership being one the most demanded areas for working during coaching sessions. Interestingly, some negative consequences of coaching are also reported, such as coachee’s goals being modified or having to deal with in-depth problems that could not be dealt with in the coaching sessions. We discuss these findings advocating for more scientific research on the mediating mechanisms responsible for its effectiveness as well as for theory-driven methodologies that can be replicated and standardized, contributing therefore to coaching effectiveness.